1994
DOI: 10.1007/bf01324873
|View full text |Cite
|
Sign up to set email alerts
|

Machine setup and component placement in printed circuit board assembly

Abstract: Abstract. Populating printed circuit .boards is one of the most costly and time-consuming steps in electronics assembly. At the beginning of each work order, three decisions are required: (1) a sequence must be specified for placing the individual components on the board; (2) tape reels must be assigned to positions on the magazine rack; and (3) a retrieval plan must be determined should the same component type be assigned to more than one magazine slot. Collectively, these problems can be modeled as a nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
(16 reference statements)
0
53
0
Order By: Relevance
“…Crama et al (2002) argued that the decision is heavily dependent on the modus operandi of the SMD placement machine. Bard et al (1994) found a strong relationship between the feeder setup and the component retrieval problem.…”
Section: Component Retrieval Plan Optimisationmentioning
confidence: 96%
See 4 more Smart Citations
“…Crama et al (2002) argued that the decision is heavily dependent on the modus operandi of the SMD placement machine. Bard et al (1994) found a strong relationship between the feeder setup and the component retrieval problem.…”
Section: Component Retrieval Plan Optimisationmentioning
confidence: 96%
“…Many researchers have modelled the component pick-and-place sequencing problem as a TSP (Drezner and Nof 1984;Gavish and Seidmann 1988;Chan and Mercier 1989;Leipa¨la¨and Nevalainen 1989;McGinnis et al 1992;Chan 1993;Bard et al 1994;Lijun 1994, 1995;Francis, Hamacher, Lee and Yeralan 1994;Khoo and Ng 1998;Tirpak et al 2000;Jeevan et al 2002;Kumar and Luo 2003;Duman and Or 2004); whilst Ball and Magazine (1988) treated it as a rural postman problem. Several researchers (Altinkemer et al 2000;Grunow, Gu¨nther, Schleusener and Yilmaz 2004) viewed the problem as a vehicle-routing problem and Leipa¨la¨and Nevalainen (1989) treated it as a three-dimensional asymmetric TSP.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations